Exploring the potential of mind joy as a Generative AI socratic tutor: fostering 21st-century skills in the general education certificate mathematics curriculum - Van Der Merwe, Joricke (School of Education, 2026)
This qualitative interpretive study explores how Artificial Intelligence (AI) has transformed many aspects of modern life, yet its potential within South Africa's General Education Certificate (GEC) Mathematics curriculum remains largely unexplored. This study aimed to explore the feasibility and potential of Mindjoy, a Socratic generative AI-enabled tutor, within the GEC Mathematics curriculum for Grade 9 learners. The focus was on understanding its impact in fostering key 21st-century skills: collaboration, communication, and critical thinking. This qualitative study is grounded in social constructivism with Laurillard's (2013a) conversational framework as an epistemological approach. Twenty-six learners were asked to complete online questionnaires on online platforms. Furthermore, the study made use of an AI-enabled Socratic learning environment, which exposed learners to two types of mathematics activities. On Day 2 of the study, 26 learners interacted with Mindjoy based on structured mathematical activities. On Day 3 of the study, 10 learners aim to solve problem-based learning activities in collaboration with Mindjoy. Data were coded through thematic inductive analysis using Discourse Analysis and Computational Grounded Theory approaches. Findings revealed that Mindjoy's ability to act as a Socratic tutor is impacted by the ability of the learners to prompt, as well as the type of mathematical activity that learners engage in. The findings highlighted that teachers need to be intentional about their choice of teaching approaches when implementing Socratic AI tutors in mathematics learning. The study illustrated that Socratic questioning delivered by Mindjoy showed potential for guided learning and elicitation; however, its full potential as an AI-powered pedagogical tool revealed limitations, especially during structured mathematical learning concepts. Recommendations include a pre- trained AI mathematics-specific tutor that will probe learners to think critically and help to maintain focus on the learning of mathematics. Additionally, it is recommended that a critical AI literacy framework be implemented to guide both teachers and learners in using AI in a useful, ethical, responsible, and respectful way. Reviewing the current GEC curriculum and assessment framework to include AI literacy as a 21st-century skill was also recommended.